Prognostic Performance of qSOFA in Pulmonary Embolism - Gurger, Mehtap; Atilgan, Fethi Ahmet; Yilmaz, Mustafa; Atescelik, Metin (Galenos Publ House, 2021)
Aim: This study aimed to investigate the role of the quick sequential organ failure assessment (qSOFA) score in determining the prognosis of patients with acute pulmonary embolism (PE). Materials and Methods: This study included patients aged >18 years who were admitted to the emergency department for complaints of shortness of breath and/or chest pain for 3 years and who were found to have acute PE on computed tomography pulmonary angiography. The qSOFA, pulmonary embolism severity index (PESI), and simplified PESI scores were calculated in patients with acute PE. During follow-up, the in-hospital mortality and requirement of intensive care continuation were determined. Results: In total, 166 patients with acute PE, of which 88 (53%) were female, were included. The mean age of the patients was 67.4 +/- 17.3 years, and 26 (15.7%) patients were admitted to the intensive care unit (ICU). The mortality rate was 9% (n=15). The predictive value of qSOFA in predicting in-hospital mortality [area under the curve (AUC) 0.907, 95% confidence interval (CI) 0.852-0.946] was similar to that of PESI (AUC: 0.846, 95% CI: 0.782-0.897) and sPESI (AUC: 0.796, 95% CI: 0.726-0.854) (p=0.23 and p=0.16, respectively). While it was superior to PESI (AUC: 0.794, 95% CI: 0.724-0.852) and sPESI (AUC: 0.721, 95% CI: 0.646-0.787) in determining the admission of patients in the ICU (AUC: 0.882, 95% CI: 0.823-0.927) (p=0.04 and p=0.01, respectively). A positive correlation was found between qSOFA and PESI (r=0.49, p=0.001) and sPESI (r=036, p=0.001). Conclusion: In this study, we found that the qSOFA score performed well in predicting in-hospital mortality and ICU admission in patients with acute PE admitted to the emergency department.
Keywords: qSOFA; pulmonary embolism; prognosis